The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1960
DOI: 10.1002/bjs.18004820705
|View full text |Cite
|
Sign up to set email alerts
|

The morbidity of subtotal thyroidectomy

Abstract: THE introduction of the antithyroid drugs and of radio-active iodine in the treatment of thyrotoxicosis has in recent years focused the attention of both surgeons and physicians on to the risks of operations on the thyroid gland. The vast majority of goitre operations performed are subtotal thyroidectomies either for simple goitre or for toxic goitre, and whilst the immediate mortality of these operations is now within acceptable limits, the post-operative complications are out of proportion to most other surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

1962
1962
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Persistent vocal cord paralysis is reported to be rare with such an operative technique 0-0.3% (4,12). This observation is also well confirmed in the comparison between our series with and without routine nerve identification, 0 and 2 %, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Persistent vocal cord paralysis is reported to be rare with such an operative technique 0-0.3% (4,12). This observation is also well confirmed in the comparison between our series with and without routine nerve identification, 0 and 2 %, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…However, the modes of Table V A routine identification of parathyroid glands is, however, no guarantee for the avoidance of postoperative hypoparathyroidism. It is not always possible to find the parathyroids (12) and in attempting to identify the glands there is always the risk of damaging their vascular supply (1).…”
Section: Discussionmentioning
confidence: 99%
“…iv) Total thyroidectomy. v) Total thyroidectomy with neck dissection 9 .The complications which is most feared is trauma to the recurrent laryngeal nerve, estimated to occur between 1 and 10% of operations 10,11 . Hypocalcaemia is uncommon after subtotal thyroidectomy but is common in the total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…This curious finding can be easily explained by the nonspecific nature of these symptoms and the possibility that they were suggested to the patients by insistent interrogation, as has also been postulated by other authors 75,76,77,78 . The only definitively hypocalcemic patient was asymptomatic, as they usually are 16,74 .…”
Section: Discussionmentioning
confidence: 87%
“…Another very significant observation is the low reliability of clinical observations when evaluating postoperative hypocalcemia in thyroidectomies. It has been reported that most hypocalcemic patients are asymptomatic 11,16,44,74,75,76,77 . This was also true in our study, since 77.8% of our hypocalcemic patients had no symptoms.…”
Section: Discussionmentioning
confidence: 99%